Pelatihan Pengolahan Ikan Bandeng Menjadi Abon sebagai Upaya Diversifikasi Produk Perikanan pada Mahasiswa INSTEKMU Tarakan - Tere, Theresia; Indrawanto, Denny; Yulianto, Agus; Mumtaza Putri, Anne; Nur Farida Haryanto, Lailin; Hidayat, Rezaldi; Rohasad, Rohasad; Giovani Siahaan, Fery; Rivaldi, Muhammadi; Gandri Haryono, M.; Firdaus, Muhammad (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
This community service activity aimed to enhance students’ knowledge and skills in diversifying fishery products through training on milkfish floss processing. Milkfish (Chanos chanos) is a fishery commodity with high economic and nutritional value and abundant production; however, its utilization in value-added processed forms remains limited. The participants of this program were ten selected students from the Institut Sains dan Teknologi Muhammadiyah Tarakan, who are expected to serve as agents for disseminating knowledge and skills in fishery product processing within the community. The activity was conducted at the Institut Sains dan Teknologi Muhammadiyah Tarakan campus using counseling, demonstration, and hands-on practice methods in milkfish floss production. The results showed an improvement in students’ understanding of the potential for milkfish product diversification, as well as enhanced skills in the floss production process, including raw material preparation, processing, and simple packaging. This training is expected to support the development of students’ entrepreneurial mindset and promote the sustainable utilization of local fishery resources